Diseño lógico de la infraestructura de red para mejorar los servicios de comunicación de la Escuela de Informática de la Universidad Nacional de Trujillo - Ramos Layza, Renzo Roberto (2013)
The data networks communication have constituted in the last years a theme of vital importance for the development of different institutions since the different services that offer the of networks communication should have a good quality of service, greater security and a good transfer. The present thesis project improved the design of the logical infrastructure of network of the information technology school of the National University of Trujillo. For this the requests for the logical design are presented, and to do an analysis of feasibility was carried out. To do an analysis of the current situation of the network communication of the information technology school, and a design is proposed logical based on the methodology of David Etheridge and Errol Simon. With this design managed to enlarge the security in the transmission of the information, so as to administer the traffic in the network to improve the services inside the environments of the school of informatics. By I finalize we leave an assembly of conclusions and recommendations that helped to fortify the project in l phase of implementation